The regional world territorial development in a global economy - Storper, Michael (New York Guilford Press, 1997)
This pioneering volume proposes a compelling new theory of how regions have sustained their economic viability in the era of multinational corporations. Unlike traditional approaches, which analyze economic systems in terms of their mechanics (inputs, outputs, prices, technology, etc.), this work views them as systems for coordinating human actions and relationships. Reconceptualizing the role of learning, technology, and local institutions in development, Storper illuminates the key role of regional economies as building blocks of the increasingly connected world.
Includes bibliographical references (p. 303-325) and index.
Keywords: Regional economics